Coral-based composite indices of sea surface temperature and salinity variability of the South Pacific Convergence Zone since 1848 - Sara Todorovic; Braddock K Linsley; Delphine Dissard; Henry C Wu (PANGAEA, 2025)
Coral-based proxy records from four long lived Porites sp. cores along the South Pacific Convergence Zone maximum precipitation diagonal axis (RO2 - Rotuma, 1F - Fiji, TNI2 - Tonga, 2R - Rarotonga) comprise the composite indices SPCZc(coral) describing the oceanographic variability of the region since 1848 CE to 1996 CE. SPCZc composite indices cover the geographic range from 12°29 extquotesingleS, 177°06 extquotesingleE (Rotuma) to 21°14 extquotesingleS, 159°49 extquotesingleW (Rarotonga). Data used in constructing the indices has been published previously (Linsley et al., 2000, 2004, 2008; Wu et al., 2013). Sub-annually resolved (8 to 12 samples per year) d18O, Sr/Ca and reconstructed d18Osw of all corals were monthly interpolated and averaged into composite indices, with calculated standard errors. Sr/Ca and d18Osw composite records were used to reconstruct sea surface temperature (SST) and sea surface salinity (SSS), calibrated against regional composite extended reconstructed sea surface temperature (ERSST, Huang et al., 2017) and SSS data from Delcroix et al. (2011), with calculated Root Mean Squared Error (RMSE) values. Composite indices extend only in the period of overlap with all four cores. This dataset provides sea surface temperature and salinity reconstructions from the South Pacific Convergence Zone extending the instrumental and gridded data products available.